Pengelolaan hutan berkelanjutan masyarakat Dayak - Fera, Dhunung Mei; Ratri, Dyah Ayu Ritma; Ishardanti, Ria (Environmental, Social, Governance and Sustainable Business, 2024)
Background: Forests are a source of life for the Dayak people. The various activities of the Dayak community towards the forest provide an understanding that the relationship between the Dayak community and the forest is an interaction that is a reciprocal relationship. Forests provide living resources to meet the needs of the Dayak people, and the Dayak people always maintain forest preservation in accordance with their culture. Grouping forests based on their function is a form of Dayak community participation in an effort to map their territory and maintain the sustainability of forest functions considering that the Dayak community's life depends on the forest. The rotational farming system is a way of managing forests for farming that has been carried out for generations by the Dayak people in a natural and traditional way. For the Dayak people, most of whom make their living as farmers, farming activities are the most suitable source of meeting their food needs. Methods: In this study, the author reviews various literature about the lives of the Dayak community in managing sustainable forests. Findings: However, over time, conversion of forest land and population growth has resulted in the conversion of forest land which results in natural damage. Policies that prioritize economic interests such as Forest Tenure Rights (HPH), Industrial Plantation Forests (HTI) change the behavior of the Dayak people and forget their traditional knowledge. Conclusion: Massive clearing of forest areas for industrial areas results in damage to the environment and ecosystem habitat, both biotic and abiotic, one way that becomes a national issue is the simultaneous occurrence of forest and land fires. Local wisdom also cannot maintain the traditional knowledge of the Dayak community which might be a solution to preserving nature. Young people who are expected to be the successors of the heritage appear to be indifferent to cultural preservation that has been proven to be sustainable. The cultural values ​​that are lived are considered a burden on the development of the times.